2006
DOI: 10.1364/oe.14.006778
|View full text |Cite
|
Sign up to set email alerts
|

Optical negative-index bulk metamaterials consisting of 2D perforated metal-dielectric stacks

Abstract: Numerical simulations of a near-infrared negative-index metamaterial (NIM) slab consisting of multiple layers of perforated metal-dielectric stacks exhibiting a small imaginary part of the index over the wavelength range for negative refraction are presented. A consistent effective index is obtained using both scattering matrix and modal analysis approaches. Backward phase propagation is verified by calculation of fields inside the metamaterial. The NIM figure of merit, [ -Re(n)/Im(n) ], for these structures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 26 publications
7
97
0
1
Order By: Relevance
“…The improved transmission property can be realized at a certain range of metal layer thickness as shown in Figure 10 (c), indicating a reduced loss in such a coupled system. This result in a certain extent explained the former results [84], and was later proved by our experimental result. Moreover, this coupling mechanism provides an encourage vision to realizing a real 3-D negative index metamaterial, which is ultimately fulfilled by X.…”
Section: Excitation Of Coupled Plasmon Modes In Two-dimensional Msupporting
confidence: 90%
See 1 more Smart Citation
“…The improved transmission property can be realized at a certain range of metal layer thickness as shown in Figure 10 (c), indicating a reduced loss in such a coupled system. This result in a certain extent explained the former results [84], and was later proved by our experimental result. Moreover, this coupling mechanism provides an encourage vision to realizing a real 3-D negative index metamaterial, which is ultimately fulfilled by X.…”
Section: Excitation Of Coupled Plasmon Modes In Two-dimensional Msupporting
confidence: 90%
“…It was numerically shown that the optical transmission loss for this negative refraction mode can even lower down by stacking more fishnet elements in the propagation direction [84]. However, the underlying physics remains obscure.…”
Section: Excitation Of Coupled Plasmon Modes In Two-dimensional Mmentioning
confidence: 99%
“…The obvious next step 30 is to stack an integer number N>1 of functional layers of the double-fishnet (2N+1 actual layers) to eventually achieve a bulk 3D uniaxial negativeindex metamaterials (see Fig. 2(a)).…”
Section: Optical Metamaterials Go Three-dimensionalmentioning
confidence: 99%
“…Among various types of NIMs, one most promising candidate is the so-called fishnet NIM which comprises of alternating metal/dielectric layers perforated with two-dimensional array of holes [11][12][13][14][15] . The simple structure also provides a feasible solution for optical NIM [16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…In the previous studies on the fishnet NIMs [11][12][13][14][15][16][17][18][19][20][21] , the light waves are incident on the top interface of the metal/dielectric multi-layers. Below the cut-off frequency of air holes the light waves can not penetrate into the structure and the negative index was retrieved within in a narrow frequency range above the cut-off.…”
mentioning
confidence: 99%